2021
DOI: 10.3390/f12040445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Exposure Time on Cambium Cell Viability In Vitro for Eucalyptus Species

Abstract: (1) Research Highlights: Thermal damage to cambium cells of Eucalyptus held in vitro was recorded at sublethal temperatures (40 °C–50 °C) when the duration of exposure extends beyond 2.5 min up to 5 min. (2) Background and Objectives: During a forest fire, heat can be transferred through tree bark potentially impacting viability of vascular cambium cells and the perennial growth of the tree. With the increased temperature of the cambium, cells are known to lose viability at temperatures exceeding 60 °C. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Temperature and time of exposure are important factors determining fire effects on plant tissues (Dickinson & Johnson 2004; Subasinghe Achchige et al . 2021) and increased fire temperatures belowground may affect not only the plant community but also the soil microbiota and the whole ecosystem functioning (Neary et al . 1999; Fontúrbel et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and time of exposure are important factors determining fire effects on plant tissues (Dickinson & Johnson 2004; Subasinghe Achchige et al . 2021) and increased fire temperatures belowground may affect not only the plant community but also the soil microbiota and the whole ecosystem functioning (Neary et al . 1999; Fontúrbel et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the number of points in which temperatures belowground exceeded the lethal threshold of cell tissue (~60°C, Daniell et al 1969) increased consistently with greater firefree intervals: 25% of points in FI-1 plots, 44% in FI-2 plots, and 75% with the greatest fire-free interval (FI-4 plots). Temperature and time of exposure are important factors determining fire effects on plant tissues (Dickinson & Johnson 2004;Subasinghe Achchige et al 2021) and increased fire temperatures belowground may affect not only the plant community but also the soil microbiota and the whole ecosystem functioning (Neary et al 1999;Font urbel et al 2012). Nonetheless, only in plots with greater fire-free intervals (FI-4) did temperatures over 60°C last around two minutes, but over 100°C they lasted for barely 30s.…”
Section: Fuel Load and Fire Temperaturesmentioning
confidence: 99%